The Influence of Parity on Blood Metabolite Profiles and Reproductive Performance in Saanen-Etawah Crossbred Does - Diatmono, Dio Fico Felsidan; Paramita, Stefani Winda; Padmawati, Fransisca Gani; Sitaresmi, Pradita Iustitia; Kumala, Seraphina; Andi, Megawati; Widyobroto, Budi Prasetyo; Suranindyah, Yustina Yuni; Freitas, Joana da Costa; Widayati, Diah Tri (Faculty of Animal Science, Universitas Gadjah Mada, 2025)
This study aimed to observe the effect of parity on the blood metabolite profiles and reproductive performance of Saanen-Etawah Crossbred does, maintained in smallholder farm. A total of 40 non-pregnant lactating does were divided into two groups: primiparous (n=16) and multiparous (n=24). The blood metabolite profiles, including total protein, glucose, cholesterol, and blood urea nitrogen (BUN), were assessed. Blood samples were collected from the jugular vein during the follicular phase, two hours prior morning feeding. Analysis of blood metabolites was carried out using photometric atomic absorption spectroscopy (AAS)-flame procedure. Furthermore, reproductive performance was observed through observing the characteristics of estrus and the length of the estrus cycle. The results indicated total protein in blood were significantly higher (p<0.05) in multiparous does (7.04±0.87 g/dL) compared to primiparous does (5.47±1.40 g/dL). In contrast, primiparous does exhibited significantly higher (p<0.05) blood cholesterol levels (122.33±30.55 mg/dL) than multiparous does (107.14±13.45 mg/dL). Multiparous does displayed typical estrus characteristics, including vulvar reddening, swelling, and vaginal mucus production, alongside a significantly shorter estrus cycle length. Parity was positively correlated with total protein levels (r=0.577), vulvar reddening (r=0.355), vulvar swelling (r=0.343), and vaginal mucus production (r=0.450), while negatively correlated with cholesterol levels (r=-0.330) and estrus cycle length (r=-0.532). These findings indicate that parity influences total protein and cholesterol levels, as well as several key estrus characteristics. Further investigation into optimized feed regimens and reproductive hormone fluctuations is warranted to enhance the reproductive efficiency of Saanen-Etawah Crossbred does.